Adaptive Smart Assembly Concept in e-Mobility: A Research Direction - Brillinger, Markus; Hadi, Muaaz Abdul; Haas, Franz; Weinzerl, Martin (European Scientific Journal, ESJ, 2020)
Achieving high total volume, high variety batch size production can be quite expensive. In this vision paper, the methodology of achieving this at low costs and the available technologies in the field of e-mobility production are described. The focus of this research lies in high adaptive and cognitive aspects in the assembly. To match the high flexibility of a Flexible Manufacturing System while considering costs, a use case of an e-axle assembly is being done. E-axle is chosen due to the ongoing electrification of mobility as the demand of mass production is low. Hence, a solution for implementing a set of methodologies for an adaptive manufacturing system with respect to assembly and implementation efforts is shown. A LoPA (Level of Practical Application) matrix is presented of all the possible adaptive technologies that are feasible to implement in the e-assembly line.